PERANCANGAN CORPORATE IDENTITY DISTRO RECKLESS STORE PADANG - ALEXANDER DASRIL, Dr. Syafwandi, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
Distro Reckless store is one of the manufacturers of menswear Reckless Store is a distro which is in the district of Padang precisely on Jl. 1 No.34 Andalas Padang, these distributions selling haberdashery products. Reckless Store was originally established with a capital of courage and daring and do not have a lot of capital and therefore owner coined the name Distro Reckless Store Design of corporate identity is taken from the character of the distributions Reckless store namely Pioneers, Dynamic, and Fresh and combined with the concept of simple and attractive that can be recognized , remembered by the target audience who later became the center of attention.Corporate identity design method Reckless store distribution is based on the absence of Corporate identity representing Reckless as distributions menswear store in Padang, western suamtera. Methods of data analysis are SWOT analysis because with this method the authors can be analyzed by using the strengths, weaknesses, opportunities, and threats so as to create a successful brand.The main media used in the design Corporate identity Reckless store distro is that media and signage manual book. Then the supporting media used, namely, business cards, posters, x-banners, pins, stickers, stamps, sales invoices, shirt, tote bag, keychainKeyword: Corporate identity, Reckless store.